Crystal structure and conductivity of bismuth-containing complex oxides - E. S. Buyanova; Yu. V. Emelyanova; M. V. Morozova; Z. A. Mikhailovskaya; O. S. Kaymieva; V. M. Zhukovskiy; S. A. Petrova (Chimica Techno Acta, 2015)
In the paper, a comprehensive systematic study of different classes of bismuth containing oxide compounds was carried out. The relationship between composition, temperature and concentration regions of existence of stable, specific structure and properties of solid solutions on the basis of vanadates, molybdates, niobates and bismuth was found. The general regularities of synthesis of solid solutions with different variants of solid-phase and soluble methods were determined. On this basis, the optimal conditions for obtaining single-phase materials were formulated. For the first time the temperature and concentration boundaries of the regions of homogeneity and areas of stable existence of polymorphic modifications of solid solutions were defined and/or refined. The structural parameters of the synthesized phases were determined. By the method of electrochemical impedance spectroscopy the nature and features of impedance spectra, the temperature and concentration dependences of electrical conductivity of ceramic materials based on bismuth containing complex oxides were identified.